Freedom riders - Nelson, Stanley, 1955-; Grant, Laurens; Arsenault, Raymond; Phillips, Tom.; Firelight Media; PBS Distribution (Firm); WGBH (Television station : Boston, Mass.); WGBH Educational Foundation ([United States] : PBS Distribution, 2011)
This inspirational documentary is about a band of courageous civil-rights activists calling themselves the Freedom Riders. Gaining impressive access to influential figures on both sides of the issue, it chronicles a chapter of American history that stands as an astonishing testament to the accomplishment of youth and what can result from the incredible combination of personal conviction and the courage to organize against all odds.
Based in part on the book Freedom riders: 1961 and the struggle for racial justice, by Raymond Arsenault.
Originally produced as a documentary in 2010.
Editors, Lewis Erskine, Aljernon Tunsil ; original music, Tom Phillips ; director of photography, Robert Shepard ; original concept developed by Paul Taylor ; series producer, Susan Bellows.
Television premiere, May 16, 2011, on the PBS series American Experience.
DVD ; NTSC, Region 1 ; widescreen presentation ; 5.1 surround audio.
Optional English SDH for the hearing impaired.
Keywords: Arsenault, Raymond -- Film adaptations; Freedom Rides, 1961.; Civil rights movements -- United States -- History; Civil rights movements -- United States -- History -- 20th century -- Personal narratives; Civil rights workers -- United States -- 20th century -- Personal narratives; Racism -- United States -- History -- 20th century; Race discrimination -- United States -- History -- 20th century; Civil rights demonstrations -- United States -- 20th century; African Americans -- Civil rights -- History -- 20th century; Segregation -- United States -- Personal narratives; United States -- Race relations -- 20th century